Response of Sesame Promising Lines (Sesamum Indicum L.) to Nitrogen in Irrigated Wetland After Paddy - Budi Hariyono; Moch. Romli (AGRIVITA, Journal of Agricultural Science, 2010)
An experiment on sesame was conducted in Nganjuk in 2005 to study the response of sesame promising lines to nitrogen in irrigated wetland after paddy. The experiment was arranged in factorial randomized block design with two factors and three replications. The first factor were two sesame lines (Si.25, Si.28) and Sbr.1 variety as control, whereas the second were five N dosage (0; 22.5; 45; 67.5 and 90 kg N/ha). Result showed that sesame in irrigated land after paddy was response to N. The respective optimum N dosages for irrigated wetland after paddy were: 83.34 kg/ha for Si.28, and 42.20 kg/ha for Sbr.1. The best N dosage for Si.25 was 22.5 kg N/ha. The superior line for irrigated land after paddy is Si.28.Keywords: Sesame (Sesamum indicum L.), nitrogen, irrigated wetland after paddy